Experience using an intermediate compiler target language for parallel machines - Papadopoulos, George A. (Microprocessors and microsystems, 1997)
The generalised computational model of term graph rewriting systems (TGRSs) has been used extensively as an implementation vehicle for a number of, often divergent, programming paradigms ranging from the traditional functional programming ones to the (concurrent) logic programming ones and various amalgamations of them, to (concurrent) object-oriented ones. More recently, the relationship between TGRSs and process calculi (such as the π-calculus) as well as linear logic has also been explored. In this paper we describe our experience in using the intermediate compiler target language Dactl based on TGRSs for mapping a variety of programming paradigms of the aforementioned types onto it. In particular, we concentrate on some of the issues that we feel have played an important role in our work (in, say, affecting performance, etc.), the aim being to derive a list of features that we feel every language model which intends to be used as an intermediate representation between (concurrent) high-level languages and (parallel) computer architectures must have.